Pengaruh User Generated Content Sharing Motives dalam Kolaborasi Lemonilo x NCT DREAM terhadap Sharing Intention Quality - Lusianna Lusianna; Sigit Pramono Hadi (Jayapangus Press, 2023)
Nowadays, business communication is growing with the presence of user generated content (UGC) as one of the communication strategies through social media. This study aims to examine the influence of UGC Sharing motives on Sharing Intention from a qualitative perspective in the Lemonilo x NCT DREAM collaboration. By 5 motives tested, Self Creation, Community Commitment, Self Expression, Social Relationship and Reward. The method used is a quantitative approach with purposive sampling as the sampling technique. The study population was Lemonilo consumers who knew of the Lemonilo x NCT DREAM collaboration with 100 respondent as a representative sample. By collecting data through surveys using online questionnaires and processig the data through the Partial Least Square (PLS) software application. The results of this study show that Self Creation, Community Commitment, Self Expression, Social Relationship and Reward have a positive effect to UGC Sharing Intention Quality. The positive effect that produced together is 75% according to the Coefficient of Determination (R2) which is 0.757. The results also showed that the Self Creation motive is most dominant in influencing users to share their content compared to other motives. Based on these findings, Lemonilo can communicate its business by increasing content sharing activities in order to direct positive and quality UGC to users.